Factors in ERP adoption : A conceptual research model - Elangovan, N.; Rajendran, Dr. R. (Journal of Contemporary Research in Management (JCRM), 2013)
Enterprise resource planning (ERP) has become the solution that supports and automates the business processes. Adoption of complex, off-the-shelf packages by different industrial vector, its suitability and realization of benefits is a challenge. ERP adoption decision is not driven by a single dominant factor, the benefits. Cost and risks of the technology rival the potential pay-offs. However, the benefit and cost analysis in ERP adoption can be moderated by external institutional forces and the  business complexity. The textile industry that is prominent in the western part of Tamilnadu has a complex processes and require real-time  interaction with the buyers and suppliers in domestic and export   operations. The reaction to ERP adoption by this industry has been mixed. This article presents a conceptual framework to understand the reasons for intention to adopt or not-adopt by the industry. The framework proposesthat benefits and risk envisaged is altered when there is institutional isomorphic pressure. Similarly, the value of benefit and degree of risk depends on the complexity of the business. The eight step Dubin’s (1978) theory development method is used for the design and validation of the conceptual research model.